GAMBARAN FAKTOR RISIKO KEJADIAN PENYAKIT INFEKSI SALURAN PERNAPASAN AKUT (ISPA) PADA BALITA DI WILAYAH KERJA UPTD PUSKESMAS BATUR 2 TAHUN 2024 - Bayu Suseno; Febriana Dwi Harjuneti (Jurnal Ilmiah Medsains, 2025)
UPTD Batur 2 Health Center is one of the health centers in Banjarnegara Regency which still has ARI problems. Based on observations from January to March2024, the prevalence of ARI is still quite high. The purpose of this study was to identify and describe the risk factors for acute respiratory infections (ARI) in children under five in the working area of UPTD Batur 2 Health Center. This research is included in desvcriptive research with cross sectional method. The population in this study were toddlers with ARI in the working area of UPTD Batur 2 Health Center who had checked themselves to the Health Center in the period January-March 2024, namely 88 toddlers with a random sampling technique. The data used in this study are primary data obtained from questionnaires and field observations and secondary data from the UPTD of Batur 2 Health Center. The results showed that most of the patiens with ARI were male (55,7%). The highest toddler age is 0-2 years (51,1%). The highest BBL is normal BBL (81,8%). Nutritional status in the good category (100%). Most of the immunization status is complete (86,4%). Good ventilation is eligible (93,2%). The density of non-dense occupancy meets the requirements (84,1%). Humadity is not good (98,8%). Mother’s level of knowledge is correct (81,8%). Good family behavior (73,9%). The conclusion from the study of patiens with ARI in infants who did not meet the requirements, namely the variables of humadity. It is hoped that the community, especially caregives, of toddlers will pay more attention to the health conditions and the surronding enviroment